Reassessing The Fraud Hexagon Model: Evidence on Its Selective Significance in Explaining Academic Fraud - Usep Syaipudin; Chara Pratami Tidespania; Rizka Malia (Jurnal Ekonomi, Manajemen, dan Bisnis, 2026)
Academic fraud is a serious issue that has the potential to undermine professional integrity, particularly in the field of accounting. This study adapts the Fraud Hexagon theory to understand the factors contributing to fraud in higher education settings. This study aims to analyze the influence of the six dimensions of the Fraud Hexagon pressure, ability, collusion, opportunity, rationalization, and ego on the propensity for academic fraud among accounting students in Bandar Lampung. A quantitative study using a cross-sectional survey design. A sample of 157 final-year accounting students from several universities in Bandar Lampung was selected using purposive sampling. Data were collected via a Google Forms questionnaire and analyzed using multiple linear regression in SPSS 25 after testing the classical assumptions. The regression results indicate that rationalization, ability, and collusion have a positive and significant effect on academic dishonesty, whereas pressure, opportunity, and ego do not. This study also makes an empirical contribution by presenting evidence based on local data from accounting students. This is important because most previous research has been dominated by non-academic contexts or different regions; thus, the findings of this study strengthen its external validity within the context of higher education in Indonesia.